ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN KARYAWAN DALAM UPAYA PENGENDALIAN INTERNAL PADA PT. JAYA SAMPURNA KONSTRUKSI - Niendya Zelly Agustina; Cholis Hidayati (Gapenas Publisher, 2023)
The purpose of this research is to find out how the Payroll Accounting Information System works at PT. Jaya Sampurna Construction and recognize how payroll systems and procedures can support internal control at PT. Jaya Perfect Construction. The object of this research is PT. Jaya Perfect Construction. This type of research is descriptive qualitative. The data used are primary data and secondary data. Primary data is in the form of information obtained directly from directors, project managers and industry finance departments. Secondary data was obtained in order to fulfill primary information such as: general description of the company, company vision and mission, industry classification and qualifications, organizational structure, and division of work tasks of PT. Jaya Perfect Construction. The results of the study show that employee attendance and payroll recording that are tried by the industry still use a manual system and have not been computerized, there is duplication of duties from the actual function, and minimal monitoring of employee attendance lists. the lack of supervision of the employee attendance list indicates that the fulfillment of the elements and objectives of internal control is still not good